1995
DOI: 10.1002/j.1460-2075.1995.tb07028.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabithorax protein is necessary but not sufficient for full activation of decapentaplegic expression in the visceral mesoderm.

Abstract: To elucidate the mechanisms by which homeotic selector (HOM) genes specify the unique features of Drosophila segments, we have analyzed the regulation of decapentaplegic (dpp), a transforming growth factor (TGF)‐beta superfamily member, and have found that the Ultrabithorax (Ubx) HOM protein directly activates dpp expression in parasegment 7 (PS7) of the embryonic visceral mesoderm. Other factors are also required, including one that appears to act through homeodomain protein binding sites and may be encoded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 56 publications
2
65
1
Order By: Relevance
“…bxd is a 40-kb region of BX-C, immediately upstream from the Ultrabithorax (Ubx) unit, and capable of exerting cis-regulatory control over expression of this unit (Lipshitz et al, 1987). It had already been shown that the TGF␤ superfamily member Dpp stimulated transcription of Ubx and that the Ubx protein was necessary but not sufficient for full activation of dpp expression (Mathies et al, 1994;Sun et al, 1995;Eresh et al, 1997). Thus, it was conceivable that a homologue of the regulatory region of Ubx might be important in TGF␤ signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…bxd is a 40-kb region of BX-C, immediately upstream from the Ultrabithorax (Ubx) unit, and capable of exerting cis-regulatory control over expression of this unit (Lipshitz et al, 1987). It had already been shown that the TGF␤ superfamily member Dpp stimulated transcription of Ubx and that the Ubx protein was necessary but not sufficient for full activation of dpp expression (Mathies et al, 1994;Sun et al, 1995;Eresh et al, 1997). Thus, it was conceivable that a homologue of the regulatory region of Ubx might be important in TGF␤ signaling.…”
Section: Resultsmentioning
confidence: 99%
“…but not sufficient for full activation of dpp expression (Mathies et al, 1994;Sun et al, 1995;Eresh et al, 1997). Thus, it was conceivable that a homologue of the regulatory region of Ubx might be important in TGF␤ signaling.…”
Section: Molecular Biology Of the Cell 4486mentioning
confidence: 99%
“…For example, genetic studies have demonstrated that full activation of the Drosophila decapentaplegic (dpp) gene depends on the presence of both, Ultrabithorax (Ubx, a Hox gene homolog) and extradenticle (exd, a homolog of PBX1) (Sun et al, 1995;Chan et al, 1994). Furthermore, it was shown that the YPWM motif of Hoxa5 is essential for the biological speci®city of this gene (Zhao et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The dppVM enhancer A 419-bp genomic segment, located 9 kilobases (kb) upstream of the coding sequence of the dpp gene, is capable of driving reporter gene expression in dpp-positive cells in parasegment 7 of the embryonic visceral mesoderm 36,37 ( Fig. 2B).…”
Section: Reverse-engineering a Transcriptional Enhancermentioning
confidence: 99%
“…(B) Embryos carrying the wild-type, 419-bp dppVM in the Ganesh-Z1 vector, 30 tains predicted binding sites for the Hox protein Ultrabithorax (Ubx) and its cofactor Extradenticle (Exd), the Wnt-responsive factor TCF, and the FoxF-related factor Biniou (Bin); all four proteins directly bind to dppVM in vitro. [37][38][39] Ubx and Exd directly activate transcription via dppVM, 37,40 while TCF acts as a Wnt-regulated transcriptional switch, activating dpp in Wnt-responding visceral mesoderm cells and repressing dpp in cells not receiving Wnt signaling. 38 However, neither ectopic Ubx/Exd nor ectopic Wnt signaling is sufficient to drive enhancer expression outside the visceral mesoderm, and dppVM is not active in other Wnt-responding or Ubx/Exd-expressing cells.…”
Section: Reverse-engineering a Transcriptional Enhancermentioning
confidence: 99%